CARRAGEENAN CHARACTERISTICS FROM HARVESTING SEAWEED (KAPPAPHYCUS ALVAREZII) WITH DIFFERENT AGES - Naiu, Asri Silvana; Mile, Lukman (Sainstek, 2011)
It has been tested against carrageenan characteristics resulting from harvesting seaweed with different ages, namely 30 days, 45 days, and 60 days. The purpose of this study was to determine the exact age of harvest in relation to the characteristics carrageenan produced from seaweed Kappaphycus alvarezii in coastal waters Desa Tolongio, Kec. Anggrek Kab. Gorontalo Utara. The research was carried out for 6 months from preparation to reporting. The method used was the explorative method, by using a Completely Randomized Design (CRD) with three replications. To determine the effect of harvest age on the characteristics carrageenan, we had tested the gel strength, viscosity, whiteness, water content, ash content and heavy metal (Hg). And to see differences between the treatment and to determine the best harvest age followed by Least Small Difference Test (LSD). All observational datas were tabulated and processed statistically using SPSS 16.0. Based on the results of research, it was known that carrageenan that was harvested of 45 days had some characteristics that approach required carrageenan for trading, namely 318.07 g/cm2 gel strength, viscosity of 101.33 cP, 10.72% ash content, and heavy metal (Hg) was not detected, whereas the water content of 23.68% and 37.2% whiteness degree was still not meet the standards of commercial carrageenan.